Eddy covariance measurements reveal a decreased carbon sequestration strength 2010–2022 in an African semiarid savanna - Aleksander Wieckowski; Patrik Vestin; Jonas Ardö; Olivier Roupsard; Ousmane Ndiaye; Ousmane Diatta; Seydina Ba; Yélognissè Agbohessou; Rasmus Fensholt; Wim Verbruggen; Haftay Hailu Gebremedhn; Torbern Tagesson (Global Change Biology, 2024)
Monitoring the changes of ecosystem functioning is pivotal for understanding the global carbon cycle. Despite its size and contribution to the global carbon cycle, Africa is largely understudied in regard to ongoing changes of its ecosystem functioning and their responses to climate change. One of the reasons is the lack of long‐term in situ data. Here, we use eddy covariance to quantify the net ecosystem exchange (NEE) and its components—gross primary production (GPP) and ecosystem respiration ( R eco ) for years 2010–2022 for a Sahelian semiarid savanna to study trends in the fluxes. Significant negative trends were found for NEE (12.7 ± 2.8 g C m 2 year −1 ), GPP (39.6 ± 7.9 g C m 2 year −1 ), and R eco (32.2 ± 8.9 g C m 2 year −1 ). We found that NEE decreased by 60% over the study period, and this decrease was mainly caused by stronger negative trends in rainy season GPP than in R eco . Additionally, we observed strong increasing trends in vapor pressure deficit, but no trends in rainfall or soil water content. Thus, a proposed explanation for the decrease in carbon sink strength is increasing atmospheric dryness. The warming climate in the Sahel, coupled with increasing evaporative demand, may thus lead to decreased GPP levels across this biome, and lowering its CO 2 sequestration.